Vibro-acoustic analysis of composite plate-cavity systems via CUF finite elements. (1st March 2021) - Cinefra, M.; Moruzzi, M.C.; Bagassi, S.; Zappino, E.; Carrera, E.
Abstract: The vibro-acoustic problem of a plate made of an advanced material, like a composite one, backed to a fluid filled cavity represents an important issue for the automotive and the aerospace sector. In fact, the noise and the vibrations prediction and then mitigation leads to an essential increase in the structural safety of the system and in the passenger comfort. Over the last thirty years, a large amount of studies has been published about the vibratory characteristics of the structure-cavity systems and, thanks to these researches, the physical phenomena linked to the reduction of noise at low frequencies is well known. Although, there is a lack of accurate numerical models, valid for innovative materials, able to describe the complex kinematic behavior of new materials and so the structural response in the low frequency range. The aim of the this work is to develop reliable finite element models for vibro-acoustic analysis of structures made of advanced materials, coupled with fluid filled cavities. The structure is described according to the Carrera's Unified Formulation (CUF), in order to enhance a wide class of powerful refined 2D plate theories with a unique formulation. The fluid cavity is described with a standard pressure-based finite element formulation of the acoustic field. The numerical results are presented for the case of a plate backed to a fluid filled cavity. Different plate layouts, in terms of materials, are considered, and also different fluids for the cavity, in order to consider both the weak and the strong coupling interaction. The results are compared with the solutions obtained by Actran®, a commercial software based on finite element method.